Implementation of Hadanah by Single Parents as A Result of Divorce in Indonesia Perspective of Maqashid Syariah and Qira'ah Mubadalah - Dede Al Mustaqim Mustaqim; Afif Muamar; Muhammad Feby Ridho Pangestu; Nazula Alfirahmah (Journal of Islamic Mubadalah, 2025)
The rising divorce rate in Indonesia has had a significant impact on family dynamics, particularly in the implementation of child custody (hadanah) by single mothers. This study aims to explore and analyze the implementation of hadanah by single mothers after divorce using the theoretical approaches of Maqashid Syariah and Qira’ah Mubadalah (as formulated by Faqihuddin Abul Kodir). Employing a qualitative method through a literature review approach, this research is designed to uncover a deep, normative, and contextual understanding of hadanah practices in Indonesia. The study is based on data sourced from journal articles, books, and relevant statistical reports (including BPS data on divorce). The findings indicate that the implementation of child custody often faces systemic issues, such as the lack of equitable financial responsibility from fathers, ultimately placing a disproportionate burden on mothers. These conditions do not fully meet the five dimensions of Maqashid Syariah (hifz ad-din, hifz an-nafs, hifz al-‘aql, hifz an-nasl, hifz al-mal), nor do they reflect the ethical principles of Qira’ah Mubadalah such as taradhin, tashawur, and mu’asyarah bil ma’ruf. Therefore, this research contributes to the discourse on gender-just custody practices within Islamic legal thought and Indonesian family law.